Filhos da Terra - Hespanha, António Manuel, author.
1 online resource (396 pages)
Keywords: Filhos da Terra narrates the history over time of the so-called ‘Portuguese communities’ living outside the boundaries of the Portuguese Empire but identified locally and by other European empires as ‘Portuguese’. Concepts such as ‘tribe’, ‘diaspora’, and ‘society of métissage’ have been widely used to define these groups. In Filhos da Terra , António Manuel Hespanha sets the stage to analyse a process of creolization that followed the Portuguese maritime expansion and consequent colonial buildup after 1415 and until 1800. This translated edition of his work opens up the possibility for future critical scholarly and public comparative discussions about diversity, identities, and identifications in the context of European empire building. Contributors are: Cátia Antunes, Zoltan Biedermann, Tamar Herzog, Noelle Richardson, Sophie Rose, and Ângela Barreto Xavier.